Atypical, Extremely Rapid Growth of Pediatric Orbital Neurilemmoma. Issue 5 (September 2021) - Vahdani, Kaveh; Luthert, Philip J.; Rose, Geoffrey E.
Abstract : Solitary orbital neurilemmoma—a benign tumor of Schwann cells in a peripheral nerve-sheath—are typically very slow growing and present in middle age; in the absence of neurofibromatosis, they are almost never seen in childhood. We describe the clinical presentation, imaging, pathology, and management of this tumor in a 12 years old—the tumor growing extremely rapidly over 5 months and without any evidence of cystic degeneration, hemorrhage, or sarcomatous features. The possibility of tumor growth having been accelerated by prior biopsy is discussed. Abstract : We report an adolescent with an extremely fast-growing solitary orbital schwannoma (neurilemmoma), the presentation, histology, and management of this possibly unique case being discussed.